Tradisi Mangain dalam Perkawinan Antara Etnik Batak Toba dengan Etnik Karo Menurut Masyarakat di Desa Pintu Angin Kecamatan Laubaleng Kabupaten Karo - Tiara Stepany Br Manurung; Puspitawati Puspitawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the stages of the mangain tradition in marriages between the Toba Batak and Karo ethnic groups in Pintu Angin Village and examines the importance of clans (marga) within the Toba Batak ethnic group. This study employed a qualitative descriptive approach, with data collection techniques including interviews, observation, and documentation. The results of this study demonstrate that the mangain tradition must be applied to marriages between the Toba Batak and Karo ethnic groups. For the Toba Batak community, clans are a vital identity, and interethnic marriages clearly hold a place within the Toba Batak traditional institution, the Dalihan Na Tolu structure. However, the mangain tradition also serves as a gateway for people outside the Toba Batak ethnic group to join the Toba Batak community. Furthermore, the Pintu Angin Village community supports this tradition as a cultural heritage that must be upheld. The mangain process is also seen as maintaining the dignity of Toba Batak customs and demonstrating mutual respect between ethnic groups.